BRANDING A BUSINESS NAME - Bulatovic, Ivan; Škorić, Sanja; Jovanović, Vladimir (Economics of Agriculture, 2016)
The process of globalization, international businesses, as well as competitive markets imposed the companies (large ones, as well as the others) to position in the required market. Making proft, which is the basic aim of every company, in such market environment can only be achieved by demonstrating distinct characteristics of a company, the characteristics which distinguish it from others with the same or similar activities. Historical and analysis of the current market have shown that being recognizable in the multitude of similar companies is a huge challenge, but also one of the main preconditions for successful operations. The moment a company is registered it acquires a specifc identity primarily owing to its business name, which distinguishes it from other companies during that frst period. Practically at the same time, the company starts creating its image or goodwill by means of several distinctive ways. One of them is branding business name or corporate branding. However, apart from large benefts, companies may also have big diffculties and risks in the same process as well.